2017
DOI: 10.1002/ehf2.12185
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal function affects clinical outcomes and management of patients with heart failure

Abstract: AimsInpatients with heart failure and renal impairment have poor outcomes and variable quality of care. We investigate treatment practice and outcomes in an unselected real‐world cohort using historical creatinine measurements.Methods and resultsAdmissions between 1/4/2013 and 30/4/2015 diagnosed at discharge with heart failure were retrospectively analysed. Stages of chronic kidney disease (CKD) and acute kidney injury (AKI) were calculated from creatinine at discharge and 3–12 months before admission. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The mortality and re-hospitalization rate of HF patients with renal insufficiency have remarkably increased compared with those of HF patients with normal renal function. [1618] A study found that ACS patients with poor renal function tended to have a higher Killip class. [19] HF is also closely related to age.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality and re-hospitalization rate of HF patients with renal insufficiency have remarkably increased compared with those of HF patients with normal renal function. [1618] A study found that ACS patients with poor renal function tended to have a higher Killip class. [19] HF is also closely related to age.…”
Section: Discussionmentioning
confidence: 99%
“…101,102,188,189 The contribution of comorbidities to patients' outcomes may be similar in patients with HFrEF, compared with those with HFpEF, 189 or be larger in those with HFpEF according to other analyses. 132 The most frequent noncardiac comorbidities include chronic kidney disease, 21,32,134,[190][191][192][193] , chronic obstructive pulmonary disease, 194 central nervous system abnormalities, 195 sleep disordered breathing, 196,197 diabetes mellitus, 65,198,199 cancer, 188,200 and iron deficiency. 60,61,63,201 They were all shown to have a major impact on clinical presentation, response to treatment and outcomes.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…In an unselected real-world cohort of 1056 admissions of 851 patients with acute HF, the prevalence of CKD stage 3A/B (moderate) was 36% whilst stage 4/5 (severe) was 11%. 2 Importantly, both severe CKD and acute kidney injury (AKI) were associated with greater inpatient mortality and length of stay compared to patients who had no or mild CKD (stage 0-2). 2 In a large meta-analysis (excluding registry studies), the prevalence of CKD at baseline was associated with higher mortality, 16% versus 11%; unadjusted odds ratio (OR) for mortality of 2.34 (95% confidence interval [CI] 2.20-2.50; P=0.001).…”
Section: Epidemiology Of Renal Impairment In Heart Failure Patientsmentioning
confidence: 99%